Urgensi Akuntansi Dalam Rumah Tangga - Nur Aisyah (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
Household accounting practices are crucial for effective financial management. Household accounting encompasses planning, recording, and decision-making. The purpose of this study is to determine the extent to which accounting instructors use accounting in household financial management and to determine the role of accounting in achieving the goal of a prosperous and harmonious household. The study was qualitative in nature and conducted using a phenomenological approach. Data analysis included data reduction, data presentation, and inference or verification. The study results indicate that household accounting planning is essential to ensure that expenses align with or do not exceed income. Recordkeeping is important, but the informant, the accounting instructor, did not yet record detailed accounting, only recording income earned, and this only at the beginning of the marriage. Family member involvement also plays a crucial role in decision-making to achieve short-term and long-term goals together, leading to a harmonious and cohesive family life.